Timing is everything: Optimal EV charging to maximize welfare - Miguel Castro (Inter-American Development Bank (IDB), 2020)
The new surge in electric vehicle (EV) charging in Texas can be served efficiently during the early morning hours with large wind generation, low electricity demand, low prices, and low environmental damage. This paper simulates the ERCOT wholesale electricity market and its environmental damages (CO2, SO2, NOx, and PM2.5) to find out how charging should be spread among hours to maximize welfare and the performance of different tariff schemes (hourly vs. day-night and private vs. social costs). The efficient charging schedule, incurring low costs and damages, is the opposite of current patterns: while users charge mostly in the evening (18-23 H), EVs should be charged during the first hours of the day (0-4 H). Constraining power withdrawals to the current Level 1 and 2 chargers reduces welfare gains since it limits using energy from those hours with lower prices and marginal damages. A day-night tariff reflecting social costs can achieve most of the gains of the first best, reducing carbon and air pollution damages below those of the current patterns.
Keywords: D62; L62; L94; Q41; Q53; Q54; R40; 330; EV charging; Wholesale electricity markets; Emissions taxes; Time-variant electricity pricing